When Jack Blinks: Si(gh)ting gay desire in Ann Bannon's Beebo Brinker - Barale, Michèle Aina (Feminist studies, college park, 1992)
The overtly lesbian story, "Beebo Brinker," by Ann Bannon offers the heterosexual male reader an opportunity to engage in nonheterosexual imaginings. Bannon's story is examined for its subcultural appropriation and subversion as a crossover novel in reverse.
https://www-proquest-com.proxy.bibliotheques.uqam.ca/docview/233183798/fulltextPDF/6501A30CCBE14AACPQ/1?accountid=14719
Keywords: approches et analyses; arts; discipline; hétérosexisme; identités LGBTQIA2+; lesbianisme; ressource en ligne; systèmes d'oppressions; études littéraires

Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

New lesbian criticism: Literary and cultural readings - Munt, Sally (Columbia University Press, 1992)
This volume explores whether there can be a specific lesbian aesthetic, juxtaposed against reading as a woman´ or as a heterosexual´. Contributors both explore the uses of recent theories such as post-structuralism and offer a lesbian critique of such methodologies. Close readings of contemporary lesbian fiction and popular culture focus on works such as Zami, Oranges Are Not the Only Fruit, The Wanderground, and Desert of the Heart as well as on lesbian pornography. Together the essays point to lesbian culture´s ability to create new meanings for iteself and to foreground the intertextuality of lesbian identities. Contributors: Sonya Andemahr, Lisa Henderson, Hilary Hinds, Katie King, Reina Lewis, Sally Munt, Gillian Spraggs, Angela Weir, Anna Wilson, Elizabeth Wilson, and Bonnie Zimmerman.
Keywords: 1900-1999; approches et analyses; arts; discipline; hétérosexisme; personnes lesbiennes; périodes historiques; systèmes d'oppressions; études culturelles; études littéraires

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Une Chambre à soi - Woolf, Virginia; Malraux, Clara (Denoël, 1992)
Bravant les conventions avec une irritation voilée d'ironie, Virginia Woolf rappelle dans ce délicieux pamphlet comment, jusqu'à une époque toute récente, les femmes étaient savamment placées sous la dépendance spirituelle et économique des hommes et, nécessairement, réduites au silence. Il manquait à celles qui étaient douées pour affirmer leur génie de quoi vivre, du temps et une chambre à soi. " Pourquoi un sexe est-il si prospère et l'autre si pauvre ? Quel est l'effet de la pauvreté sur le roman ? " Virginia Woolf
Section: 171 pages ; 21 cm
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; europe; lit2815; lit3220; lit3495; premier cycle; périodes historiques; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires